Turnover Intention in Healthcare Workers: An Investigation of Work Environment, Employee Performance, And Work Satisfaction Us Mediating Role - Winda Widyanty; Prita Prasetya (Universitas Mercu Buana, 2023)
Every company, including in the health industry, needs quality human resources (employees) in carrying out its operational activities. Employees are the organization's main asset and have a strategic role in the organization, namely as thinkers, planners, and controllers of organizational activities. We investigated the turnover rate of healthcare workers in terms of the work environment, employee performance, and job satisfaction as a mediating role. We tested our hypothesis using SEM/PLS on 75 respondents who worked in healthcare companies and found that the work environment, employee performance, and job satisfaction influence the turnover intention of employees who work in the health sector.